2015
DOI: 10.46654/ij.24889849.a688
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ Competence and Utilization of Social Media in Science Teacher Education

Abstract: The study investigated Educators' competence and utilization of social media in science teacher education. The study was carried out in Alvan Ikoku Federal College of Education, Owerri, Imo state. Based on the purpose of the study, 2 research questions guided the study. The population of the study consists of all the Educators in school of science of the Institution. Based on the size of the population of the educators in school of science, they were all used as sample for the study. The descriptive survey res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…This is suspected to emanate from the consistent clamor by school authorities mandating educators to present their lectures through digital avenues. The result is in line with Nwoke, et al (2020) which revealed that educators are moderately competent with the use of social media platforms for personal purposes such as communications, information, sourcing of academic materials, and other social factors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is suspected to emanate from the consistent clamor by school authorities mandating educators to present their lectures through digital avenues. The result is in line with Nwoke, et al (2020) which revealed that educators are moderately competent with the use of social media platforms for personal purposes such as communications, information, sourcing of academic materials, and other social factors.…”
Section: Discussionsupporting
confidence: 84%
“…The success of digital technologies application in higher education system is dependent on the educators and their level of competence on handling the digital devices. Nwoke, Ikwuanusi and Onuoha (2020) citing Orji and Abolarin, referred to competence as the effectiveness or ability of anyone concerned to apply the acquired knowledge and skill to achieve desired results.…”
mentioning
confidence: 99%